2020
DOI: 10.1155/2020/6890601
|View full text |Cite
|
Sign up to set email alerts
|

GPS Data in Urban Online Car-Hailing: Simulation on Optimization and Prediction in Reducing Void Cruising Distance

Abstract: Ride-hailing, as a popular shared-transportation method, has been operated in many areas all over the world. Researchers conducted various researches based on global cases. They argued on whether car-hailing is an effective travel mode for emission reduction and drew different conclusions. The detailed emission performance of the ride-hailing system depends on the cases. Therefore, there is an urgent demand to reduce the overall picking up distance during the dispatch. In this study, we try to satisfy this dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Theoretical studies show great promise of ride-hailing for reducing deadheading, VMT, and ultimately emissions. Wang et al [57] perform an optimization with deep learning neural network to minimize deadheading. Simulations with DiDi Chuxing data from Chengdu, China, show the system can reduce picking up distance by 7.5%.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Theoretical studies show great promise of ride-hailing for reducing deadheading, VMT, and ultimately emissions. Wang et al [57] perform an optimization with deep learning neural network to minimize deadheading. Simulations with DiDi Chuxing data from Chengdu, China, show the system can reduce picking up distance by 7.5%.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Set the initial arrival rate of drivers λ 0 � 2500 vehicles/h, the initial arrival rate of passengers μ 0 � 5000 Passengers/h, the average travel time t � 0.5 hours, and the probability of drivers leaving the system q leave � 0.8. Assuming the psychological expected price of drivers and passengers f c , f V ∼ N (3,1). e driver cost is 1.11 yuan/km, and the platform cost is 0.14p.…”
Section: Example Setupmentioning
confidence: 99%
“…Ride-hailing, referring to the activity of calling a vehicle or driver to go to a destination, rises in many metropolitan areas and takes a considerable part of mobility services [1]. e online ride-hailing platform is a subversion of the traditional travel industry in the context of the Internet; it transmits the traditional service mode from the driver side to the passenger side by the combination of online information and offline experience [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al found that Shanghai presents a two-level hierarchical polycentric urban structure feature by applying a spatial embedded network model [40]. To build the original destination (OD) matrix, the common types of traffic analysis unit, include regular grids [41][42][43][44][45], hexagons [46], and irregular polygons (usually obtained by dividing the road network or district boundary). In particular, the regular grid is the most common due to its advantages, such as ease of use and visualization.…”
Section: Introductionmentioning
confidence: 99%